Relationships, love and sexuality: what the Filipino teens think and feel - de Irala Jokin; Osorio Alfonso; del Burgo Cristina; Belen Vina A; de Guzman Filipinas O; Calatrava María; Torralba Antonio N (BMC, 2009)
Abstract Background In order to achieve a change among teens' sexual behavior, an important step is to improve our knowledge about their opinions concerning relationships, love and sexuality. Methods A questionnaire including topics on relationships, love and sexuality was distributed to a target population of 4,000 Filipino students from third year high school to third year college. Participants were obtained through multi-stage sampling of clusters of universities and schools. This paper concentrates on teens aged 13 to 18. Results Students reported that they obtained information about love and sexuality mainly from friends. However, they valued parents' opinion more than friends'. They revealed few conversations with their parents on these topics. A majority of them would like to have more information, mainly about emotion-related topics. Almost half of respondents were not aware that condoms are not 100% effective in preventing STIs or pregnancies. More girls, compared to boys, were sensitive and opposed to several types of sexism. After adjusting for sex, age and institution, the belief of 100% condom effectiveness and the approval of pornography and sexism were associated with being sexually experienced. Conclusion There is room for further encouraging parents to talk more with their children about sexuality, specially aspects related to feelings and emotions in order to help them make better sexual choices. Indeed, teens wish to better communicate with their parents on these issues. Condoms are regarded as safer than what they really are by almost half of the participants of this study, and such incorrect knowledge seems to be associated with sexual initiation.